Application of rigid bronchoscopy for emergent removal of tracheobronchial foreign body in paediatric cases: a learning curve study. Issue 11 (16th November 2022) - Bin, X; Liu, L; Fang, Q; Tan, SH; Tang, AZ
Abstract: Objectives: To explore the factors associated with the operative duration for paediatric tracheobronchial foreign body removal by rigid bronchoscopy, and to analyse the learning curve for mastery of the rigid bronchoscopy skill. Methods: A retrospective study was performed of paediatric cases of tracheobronchial foreign body removal by rigid bronchoscopy in our department from January 2007 to July 2019. Multivariate Cox regression analysis was used to analyse the factors associated with the operative duration. In addition, the learning curves for two doctors were evaluated by curve-fitting regression analysis. Results: A total of 410 paediatric cases of tracheobronchial foreign body removal by rigid bronchoscopy were evaluated. The operative duration was significantly influenced by the skill of the doctor. The learning curves for both doctor A and doctor B demonstrated two typical phases: an initially rapidly changing learning phase followed by a steady consolidation phase. Conclusion: The operative duration for paediatric tracheobronchial foreign body removal by rigid bronchoscopy was associated with the skill of the doctor. In order to fully master the rigid bronchoscopy technique, doctors should perform a minimum number of procedures to pass the learning phase and reach the consolidation phase.